The optimal PEEP after alveolar recruitment maneuver assessed by electrical impedance tomography in healthy horses - Andrade, Felipe Silveira Rego Monteiro; Ambrósio, Aline Magalhães; Rodrigues, Renata Ramos; Faccó, Lara Lopes; Gonçalves, Lucas Alaião; Garcia Filho, Sérgio Grandisoli; dos Santos, Rosana Thurler; Rossetto, Thais Colombo; Pereira, Marco Aurélio Amador; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2022)
Background Electrical impedance tomography (EIT) has been an essential tool for assessing pulmonary ventilation in several situations, such as the alveolar recruitment maneuver (ARM) in PEEP titration to maintain the lungs open after atelectasis reversion. In the same way as in humans and dogs, in horses, this tool has been widely used to assess pulmonary aeration undergoing anesthesia, mechanical ventilation, recruitment maneuver, standing horses, or specific procedures. Objectives The present study aimed to evaluate the distribution of regional ventilation during ARM based on lung monitoring assessment by EIT, with a focus on better recruitment associated with less or no overdistention. Methods Fourteen horses of 306 ± 21 kg undergoing isoflurane anesthesia in dorsal recumbency were used. The animals were mechanically ventilated with a tidal volume of 14 ml kg−1 and a respiratory rate of 7–9. An alveolar recruitment maneuver was instituted, increasing the PEEP by five cmH2O every 5 min until 32 cmH2O and decreasing it by five cmH2O every 5 min to 7 cmH2O. At each step of PEEP, arterial blood samples were collected for blood gas analysis, EIT images, hemodynamic, and respiratory mechanics. Results Associated with the CoV-DV increase, there was a significant decrease in the DSS during the ARM and a significant increase in the NSS when PEEP was applied above 12 cmH2O compared to baseline. The ComplROI showed a significant increase in the dependent area and a significant decrease in the non-dependent area during ARM, and both were compared to their baseline values. The driving pressure decreased significantly during the ARM, and Cst, PaO2, and PaO2/FiO2 ratio increased significantly. The VD/VT decreased significantly at DEPEEP17 and DEPEEP12. There was an HR increase at INPEEP27, INPEEP 32, and DEPEEP17 (p < 0.0001; p < 0.0001; and p < 0.05, respectively), those values being above the normal reference range for the species. The SAP, MAP, DAP, CI, and DO2I significantly decreased INPEEP32 (p < 0.05). Conclusion The ARM by PEEP titration applied in the present study showed better ventilation distribution associated with better aeration in the dependent lung areas, with minimal overdistention between PEEP 17 and 12 cmH2O decreasing step. Those changes were also followed by improvements in static and regional compliance associated with increased oxygenation and pulmonary ventilation. ARM promoted a transitory decrease in arterial blood pressure and depression in CI with a concomitant drop in oxygen delivery, which should be best investigated before its routine use in clinical cases.